2021
DOI: 10.3389/fimmu.2021.787565
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 Enhances C-Fiber-Mediated and Blue Light-Induced Spontaneous Pain in Female Mice

Abstract: The incidence of chronic pain is especially high in women, but the underlying mechanisms remain poorly understood. Interleukin-23 (IL-23) is a pro-inflammatory cytokine and contributes to inflammatory diseases (e.g., arthritis and psoriasis) through dendritic/T cell signaling. Here we examined the IL-23 involvement in sexual dimorphism of pain, using an optogenetic approach in transgenic mice expressing channelrhodopsin-2 (ChR2) in TRPV1-positive nociceptive neurons. In situ hybridization revealed that compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…This phenomenon was further confirmed by subsequent studies from other groups [23,24,42]. IL-23 in macrophage signaling induced significantly greater p38 phosphorylation, a marker of nociceptor activation, in DRGs of female than male mice and enhanced C-fiber-mediated and blue light-induced spontaneous pain in female, but not male, mice [19,20]. Resolvins D5 repressed neuropathic and inflammatory pain in male, but not female, mice likely through targeting immune cells (e.g., macrophages) in DRG [21].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This phenomenon was further confirmed by subsequent studies from other groups [23,24,42]. IL-23 in macrophage signaling induced significantly greater p38 phosphorylation, a marker of nociceptor activation, in DRGs of female than male mice and enhanced C-fiber-mediated and blue light-induced spontaneous pain in female, but not male, mice [19,20]. Resolvins D5 repressed neuropathic and inflammatory pain in male, but not female, mice likely through targeting immune cells (e.g., macrophages) in DRG [21].…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have demonstrated that several intracellular signals are involved in the sexual dimorphism of pain. IL-23 augmented C-fiber-mediated and blue light-induced spontaneous pain in female, but not male, mice [19,20]. Resolvins D5 repressed neuropathic and inflammatory pain in male, but not female, mice [21].…”
Section: Behavioral Testsmentioning
confidence: 90%
“…In 2017, a new in-spinal optogenetics device was used for pain treatment and research ( Table 1 and Figure 3 ; Samineni et al, 2017 ; Mai et al, 2020 ). Using this device, the researchers activated the afferent nerve of trpv1-chr2 channel protein, causing pain response behavior in mice ( Jacob and Szerb, 1951 ; Zhu et al, 2020 ; Ji et al, 2021 ; Zhang et al, 2021 ). The researchers then ran a real-time comparison experiment, and the results were the same.…”
Section: Nervous System-based Clinical Researchmentioning
confidence: 99%
“…Macrophages are professional phagocytes responsible for the removal of dying or dead cells and cellular debris; they are mainly derived from circulating monocytes [54]. Increasing evidence has suggested that macrophages play an essential role in the initiation, maintenance, and resolution of chronic pain, depending on the location, stage, and phase of macrophages, respectively [25,29,30,32,[55][56][57]. Furthermore, macrophages are also involved in the sex dimorphism of chronic pain through modulating the IL23/IL17A axis at the peripheral terminal ends of DRG neurons [57].…”
Section: Regulation Of Cpap By Macrophage Infiltration and Pro-inflam...mentioning
confidence: 99%